Features of the biochemical parameters of blood and exudates during tubercular exudative pleurisy - Ye. A. Yuriyeva; O. V. Voronkova; O. I. Urazova; V. V. Novitsky; Ye. V. Nekrasov; Yu. V. Kolobovnikova; T. V. Fedorovich; Z. K. Khaitova; I. O. Naslednikova (Бюллетень сибирской медицины, 2012)
Some biochemical indicators of peripheral blood and pleural fluid (level of the total protein, glucose, lactate dehydrogenase activity) at patients with various variants of tubercular exudative pleurisy (MBT-positive and MBT-negative) for the purpose of definition of possibility of use this indicators as criteria for differential diagnostics of a pleurisy, have been studied. It has been established that tubercular exudative pleurisy is characterized by the expressed changes of the biochemical status of blood and pleural fluid in comparison with that at healthy donors and patients with not tubercular exudative pleurisy, however, this changes in most cases are nonspecific and don't depend on a variant of tubercular exudative pleurisy.